Implications of Monitoring and Evaluation for Improving School Quality - Hidayah, Neneng Nur; Pulungan, Desriyanti; Elfrianto, Elfrianto (Indonesian Journal Education, 2023)
One of the educational subsystems in schools that has a direct relationship with other educational subsystems is monitoring and evaluation. This literature review aims to analyze the implications of monitoring and evaluation of school quality. The results of monitoring and evaluation consist of data about many aspects such as the state of curriculum implementation, teacher work, student performance, and so on. These data are used as building blocks for program improvement and purification so that student learning outcomes are expected to increase. Student accomplishments and other data are used as building blocks for program enhancement, with the goal of raising the anticipated level of educational quality.